Collusion Sustainability with a Capacity Constrained Firm - Leonardo Madio; Aldo Pignataro (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study an infinitely repeated oligopoly game in which firms compete on quantity and one of them is capacity constrained. We show that collusion sustainability is non-monotonic in the size of the capacity constrained firm, which has little incentive to deviate from a cartel. We also present conditions for the emergence of a partial cartel, with the capacity constrained firm being excluded by the large firms or self-excluded. In the latter case, we show under which circumstances the small firm induces a partial conspiracy that is Pareto-dominant. Implications for cartel identification and enforcement are finally discussed.
Keywords: D21; L13; L41; 330; antitrust; capacity constraints; collusion; partial cartel